Early neonatal mortality and neurological outcomes of neonatal resuscitation in a resource-limited setting on the Thailand-Myanmar border: A descriptive study - Janet, S; Carrara, V; Simpson, J; Thin, N; Say, W; Paw, N; Chotivanich, K; Turner, C; Crawley, J; McGready, R (Public Library of Science, 2018)
Background Of the 4 million neonatal deaths worldwide yearly, 98% occur in low and middle-income countries. Effective resuscitation reduces mortality and morbidity but long-term outcomes in resource-limited settings are poorly described. This study reports on newborn neurological outcomes following resuscitation at birth in a resource-limited setting where intensive newborn care including intubation is unavailable. Methods Retrospective analysis of births records from 2008 to 2015 at Shoklo Malaria Research Unit (SMRU) on the Thailand-Myanmar border. Findings From 21,225 newbonrs delivered, 15,073 (71%) met the inclusion criteria (liveborn, singleton, ≥28 weeks’ gestation, delivered in SMRU). Neonatal resuscitation was performed in 460 (3%; 422 basic, 38 advanced) cases. Overall early neonatal mortality was 6.6 deaths per 1000 live births (95% CI 5.40–8.06). Newborns receiving basic and advanced resuscitation presented an adjusted rate for death of 1.30 (95%CI 0.66–2.55; p = 0.442), and 6.32 (95%CI 3.01–13.26; p<0.001) respectively, compared to newborns given routine care. Main factors related to increased need for resuscitation were breech delivery, meconium, and fetal distress (p<0.001). Neurodevelopmental follow-up to one year was performed in 1,608 (10.5%) of the 15,073 newborns; median neurodevelopmental scores of non-resuscitated newborns and those receiving basic resuscitation were similar (64 (n = 1565) versus 63 (n = 41); p = 0.732), while advanced resuscitation scores were significantly lower (56 (n = 5); p = 0.017). Interpretations Newborns requiring basic resuscitation at birth have normal neuro-developmental outcomes at one year of age compared to low-risk newborns. Identification of risk factors (e.g., breech delivery) associated with increased need for neonatal resuscitation may facilitate allocation of staff to high-risk deliveries. This work endorses the use of basic resuscitation in low-resource settings, and supports on-going staff training to maintain bag-and-mask ventilation skills.